2018
DOI: 10.1371/journal.pone.0200570
|View full text |Cite
|
Sign up to set email alerts
|

Absence of IL-10 production by human PBMCs co-cultivated with human cells expressing or secreting retroviral immunosuppressive domains

Abstract: Immunosuppression by retroviruses including the human immunodeficiency virus—1 (HIV-1) is well known, however the mechanisms how retroviruses induce this immunosuppression is not fully investigated. It was shown that non-infectious retroviral particles as well as retroviral or recombinant retroviral transmembrane envelope (TM) proteins demonstrated immunosuppressive properties. The same was shown for peptides corresponding to a highly conserved domain in the TM protein. This domain is called immunosuppressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This consideration is relevant because an emerging variant could possibly cause an altered expression when fused to the tANCHOR system. Since similar effects have not yet been observed for other proteins displayed using the tANCHOR display technology, we can only presume that further SARS-CoV-2 RBD variants will likewise be displayed on the cell surface, as this study has shown [ 24 , 27 , 48 , 58 ]. Antibody-binding capability is another significant drawback of this kind of developed assay.…”
Section: Limitations and Prerequisitesmentioning
confidence: 62%
See 2 more Smart Citations
“…This consideration is relevant because an emerging variant could possibly cause an altered expression when fused to the tANCHOR system. Since similar effects have not yet been observed for other proteins displayed using the tANCHOR display technology, we can only presume that further SARS-CoV-2 RBD variants will likewise be displayed on the cell surface, as this study has shown [ 24 , 27 , 48 , 58 ]. Antibody-binding capability is another significant drawback of this kind of developed assay.…”
Section: Limitations and Prerequisitesmentioning
confidence: 62%
“…In this study, we focused on detecting antibodies derived from clinical samples directed against the RBD of SARS-CoV-2. Although we previously demonstrated in principle that it is possible to detect purified antibodies directed against epitopes 2F5/4E10 and the immunosuppressive domain (ISU) of HIV-1 by using the tANCHOR system, it was still unclear whether clinical samples could also be screened [ 23 , 24 ]. Therefore, we optimized this cell-based ELISA approach by employing the tANCHOR system to monitor IgG from clinical samples by using serum samples containing antibodies against the S protein of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 , 21 In particular, the transmembrane anchors derived from the Tspan CD82 showed best performance for displaying proteins on the cell surface of human embryonic kidney 293T (HEK293T) or HeLa cells, where the protein of interest is fused and expressed as a chimeric-membrane-bound unit connected by optimized linker sequences between the third and fourth TM. 21 , 22 For testing the neutralization activity of an SARS-CoV-2 variant, only the coding DNA sequence in the tANCHOR vectors has to be adjusted. This enables rapid adaptation to upcoming SARS-CoV-2 variants.…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylation of proteins is very critical as shown for HIV when neutralizing antibodies should be raised against native viral protein structures [ 14 ]. To meet the requirements for a fast and efficient immunization approach including posttranslational modification of the antigen, we employed the tetraspanin (Tspan) anchor (tANCHOR) system [ 15 , 16 ]. This system is based on the use of transmembrane domains derived from the Tspan superfamily where a protein of interest is fused and expressed as a chimeric membrane-bound protein displayed on the surface of human cells.…”
Section: Introductionmentioning
confidence: 99%